“Suffering in Deafening Silence”: Suicide Ideation and Attempted Suicide in the Lives of Incarcerated Rural West Virginia Girls - Freeman, Mackenzie (The prison journal, 2024)
Complex trauma history is one of the incarcerated girls’ most salient characteristics, and two of the most injurious outcomes are suicide ideation and attempted suicide. However, to the best of our knowledge, not one published study has thus far focused on the suicide experiences of rural girls in detention facilities. Guided by theoretical perspectives on females’ pathways into crime and using data derived from in-depth semistructured interviews with 39 girls housed in two West Virginia detention centers, the main objective of this article is to help fill a major gap in the extant literature on rural girls in conflict with the law. The key themes that emerged from qualitative data analyses are sleep deprivation, substance use, and a history of sexual and physical abuse.